The phytogenetic resources of pineapple (Ananas comosus var. Comosus (L.) Merr.) in Cuba - Rodríguez Alfonso, Daymara (2020)
The phytogenetic resources for food and agriculture constitute the biological basis of the world’s food safety and the sustenance of world population. These resources are the most important raw material of the phyto-enhancers and the most indispensable contribution for farmers.Conservation in situ is being increasingly affected, and it is for this reason that training activities are carried out to sensitize the local population to safeguard diversity. In the past years the ex situ conservation alternatives have increased, particularly, the long-term ones and the molecular characterization and identification of the varieties withmolecular markers techniques in which iso-enzymes up to genome sequencing have been used. The pineapple germplasm is mainly maintained in three great collections located in Brazil, Martinique and Hawaii. In Cuba, the genetic base of the species is not extensive, and only the horticultural groups of Hispaniola, Cayenne and Pernambuco are represented. The predominant variety is the ‘Red Spanish’, while the While Pineapple and some Cayenne pineapples are the least grown, so their perpetuity could be endangered. The largest areas for the growing of pineapples in the country belong to the state, but the greatest diversity is kept by the farmers.